Reduced membrane damage and higher lea protein content under low temperature: Probable causes for delayed defoliation of Hevea in North East India - Ray D; Das G; Dey S K; Raj S (Natural Rubber Research, 2004)
Two popular clones of Hevea brasiliensis were studied to understand their defoliation pattern in relation to some of the biochemical parameters during the winter season. The low temperature induced changes such as membrane injury, anthocyanin and late embryogenesis abundant (LEA) protein accumulation were examined. The early defoliation clone RRII 105 showed high membrane injury, anthocyanin accumulation and rapid chlorophyll degradation with low LEA protein, whereas the late defoliating clone RRIM 600, recorded the opposite trend. It can be inferred that the temporal difference in wintering and in the biochemical parameters studied are related to cold susceptibility
Keywords: Anthocyanin; Chlorophyll; Defoliation; Hevea brasiliensis; LEA protein; Membrane damage